Aplicativos de redes sociais: uso excessivo, preocupação cognitiva e consequências negativas - Rosa, Ana Claudia da (2017)
With the evolution of the Web and the expansion of social networking sites, new technologies and mobile information devices - smartphones, tablets, among others - have shown a constant growth in recent years in Brazil and in the world, creating a new possibility of working the access to mobile information (F/NAZCA; SAATCHI; SAATCHI, 2013). Therefore, the current research was based on the adaptation of the theoretical model proposed by Zheng and Lee (2016), whose authors used Davis's (2001) Internet Pathological Use Model (UPI) to examine the sequential process of problematic use of social networking applications. A quantitative and descriptive research was carried out with the data collection performed through the survey technique with a sample of 340 youngsters of the Generation Z, being high school students of three Colleges of the private network of Santa Maria/RS and the Instituto Federal Farroupilha – Campus of Júlio de Castilhos (IFFar/JC). The study aimed to investigate the impact of overuse and cognitive concern on the negative consequences of the use of social networking applications on young people of the Generation Z. When performing the statistical validation and attesting the internal reliability of the research model, the formation of five factors. Afterwards, it was evidenced that the factors "use and tension" and cognitive concern have a positive and significant impact on the negative consequences of the use of social network applications. The largest relation, revealing the greatest impact of the model occurred between the "use and tension" factor and the conflict factor between technology and social life. The smallest impact was found between cognitive concern factors and conflict between technology and personal life. As theoretical contributions, we emphasize the deepening and theoretical adaptation of the model of Zheng and Lee (2016), in addition to the integration of a new construct in its measurement. From the practical point of view, the study sought to provide school managers with knowledge of the behavior of young people of the Generation Z against the use of social networking applications. Despite the limitations, it is considered that the present dissertation has contributed to the expansion of research on the dark side and negative consequences of the use of social network applications, as well as, it is expected that it can serve as a base and help in the accomplishment of future studies about this theme.